Human Pharmaceuticals in the Environment Current and Future Perspectives - Brooks, Bryan W.; Huggett, Duane B.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Fish on Prozac. Drugs found in drinking water. India’s drug problem. Chances are you’ve seen these headlines. Human pharmaceuticals represent environmental contaminants of emerging concern, and receive unprecedented attention from the scientific, regulatory and public sectors.  This timely contribution, prepared by international experts in the field, synthesizes and critically examines topics ranging from regulations, environmental chemistry and exposure analysis, to comparative pharmacology, environmental toxicology, water treatment technologies and pharmaceutical take back programs. Compared to historical contaminants, chemical and biological attributes of human pharmaceuticals present unique challenges to environmental management, but lessons learned from the study of pharmaceuticals promise to advance prospective and retrospective approaches to assess the impacts of industrial chemicals. Students and environmental scientists, managers, regulators, and public health professionals will benefit from this forward-thinking treatment of human pharmaceuticals in the environment.
Perspectives on Human Pharmaceuticals in the Environment -- Environmental Risk Assessment for Human Pharmaceuticals – the Current State of International Regulations -- Regulation of Pharmaceuticals in the Environment: The United States -- Environmental Fate of Human Pharmaceuticals -- Environmental Comparative Pharmacology: Theory and Application -- A Look Backwards at Environmental Risk Assessment: An Approach to Reconstructing Ecological Exposures -- Considerations and Criteria for the Incorporation of Mechanistic Sub-Lethal Endpoints into Environmental Risk Assessment for Biologically Active Compounds -- Human Health Risk Assessment for Pharmaceuticals in the Environment: Existing Practice, Uncertainty, and Future Directions -- Wastewater and Drinking Water Treatment Technologies -- Pharmaceutical Take Back Programs -- Index.
Keywords: Ecotoxicology; Pharmacology; Environmental management; Analytical chemistry; Ecotoxicology; Pharmacology/Toxicology.; Environmental Management; Analytical Chemistry